Pengaruh Lingkungan Kerja,Motivasi Kerja Dan Disiplin kerja Terhadap Kinerja Karyawan Pada Bank Syariah Mandiri Surakarta (Mikro) - Ambarwati, Vicky, Imron Rosyadi, S.E, M.Si (2016)
This study aims to examine and analyze the influence of the working environment, motivation and discipline on the performance of employees at Bank Syariah Mandiri Surakarta (Micro). Data collected through questionnaires carried out on 50 employees of Bank Syariah Mandiri Surakarta (Micro). Analysis of the data in this study using Linear Regression Analysis Berganda. Setelah conduct a literature review and formulation of hypotheses, data collected through questionnaires in 50 employees of Bank Syariah Mandiri Surakarta obtained using random sampling techniques, then analysis of data obtained using multiple linear analysis. This analysis included: validity and reliability test, classical assumption (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis and goodness of fit (test F, the coefficient of determination / R square, t-test). Where the employee performance variable (Y), work environment (X1), motivation (X2), work discipline (X3) were tested by t-test showed that the three independent variables significantly influence the decision of the dependent variable. Then through the F test showed that there is influence between work environment, motivation and discipline of work on employee performance. Keywords: employee performance, work environment, work discipline